Change in peripapillary and macular choroidal thickness change in children with type 1 diabetes mellitus without visual impairment or diabetic retinopathy. Issue 2 (17th August 2019) - Li, Tao; Jia, Yan; Wang, Shanshan; Xu, Yi; Yin, Yao; Wang, Anken; Gao, Lu; Xu, Xian; Yang, Chenhao; Zou, Haidong
Abstract: Purpose: To study the characteristics of choroid thickness (CT) of the optic disc and macula in children with type 1 diabetes mellitus (T1DM) without visual impairment and diabetic retinopathy (DR) and analyse associated factors. Methods: A square area of 6 × 6 mm around the centre of the optic disc and macula was scanned. The indices analysed mainly included CT at the macular centre (1 mm), and temporal, superior, nasal or inferior aspect of the inner ring (1–3 mm) and outer ring of (3–6 mm) optic disc and macula. Independent risk factors were analysed using multifactor linear regression. Results: A total of 44 children with T1DM and 48 healthy subjects were enrolled. The diabetic group showed significant increase in the inferior inner ring of parapapillary CT (100.99 ± 30.42 μ m versus 89.41 ± 34.00 μ m, p = 0.04) and nasal outer ring of parapapillary CT (157.02 ± 47.35 μ m versus 131.15 ± 35.17 μ m, p = 0.01) as compared to those values in the healthy controls. Spherical equivalent refraction and family history of hypertension are independent factors of both peripappillary choroid thickness (PPCT) and macular choroid thickness (PMCT). Spherical equivalent refraction (p = 0.01) and serum cholesterol (p = 0.03) were independent factors of the inferior inner ring of parapapillary CT, whereas family history of hypertension was an independent factor of the nasal outer ring of parapapillary CT (p = 0.001). Conclusion: In children with diabetes without DR or visual impairment, the CT increase in nasal outer ring of parapapillary (PPNO) and the inferior inner ring of parapapillary (PPII) may be the characteristic pre‐DR alteration at the early stage of DM. For children with higher serum cholesterol and family history of hypertension, the change of the nasal outer ring of parapapillary CT and the inferior inner ring of parapapillary CT may be more advanced.